Analysis the Influence of ROE, DER, Inflation and Exchange Rate on LQ45 Company Price 2013-2017 Period - Gilang Oktario Wicaksana; Antyo Pracoyo (Indonesia Banking School, 2019)
This study aims to test, analyze, and conclude the influence of Return on Equity (ROE), Debt to Equity Ratio (DER), Inflation, and Exchange Rates on the Company's Stock Prices which included in the LQ-45 index. This research was conducted during 2013-2017. The type data in this study is secondary data which is a collection of data obtained on Indonesia Stock Exchange and Bank Indonesia website. The selection of data samples using purposive sampling method and the result shows sample of 19 company stock which included in the LQ-45 index for 5 consecutive years (2013-2017). The analysis technique used in this study is panel data modeling (multiple linear regression analysis) with EViews analysis tool version 9. The re-sults show that the ROE variable has a significant positive effect, the DER variable has a negative and sig-nificant influence, and the exchange rate has a positive and significant effect on the LQ-45 Share Price dur-ing 2013 - 2017.Keywords: Return to Equity, Debt to Equity Ratio, Exchange Rate, Stock Price